An Analyzing critical thinking skills using the context of the learning package for students of Madrasah Tsanawiyah Negeri 2 Jambi - diah dwi santri (Universitas PGRI Semarang, 2023)
Indonesia is a country that is also a participant in PISA, the fact is that even though it has known PISA for a long time, it still experiences a slump, especially the upper level PISA caused by many factors. Among them can be seen in the findings of PISA in 2018 where Indonesiais in the Low Perfomence quadrant with High Equity, then also Gender Gap Performance and also learning conditions in schools that are still in the zone of very simple math problems. This concludes that students in schools have not fully explored cognitive abilities in solving mathematical problems that are analytical, especially. The problem of low mathematical ability of students in solving a contextual problem in mathematics learning is the biggest problem in mathematics education in Indonesia. This study aims to analyze the critical thinking ability of students using the context of learning packages. This research is a quantitative descriptive type with the population of this study is students of class VIII Madrasah Tsanawiyah Negeri 2 Jambi City. The data collected is Student test results.